A study on morbidity and mortality pattern of poisoning in tertiary care hospital - Paranthakan, C.; Govindarajan, P. K. (International Journal of Research in Medical Sciences, 2017)
Background: The poisoning due to various reasons commonly occurs among population. Normally tertiary care hospitals receive large numbers of referral. During treatment many die due to poisoning. Objectives of the study were to find out the magnitude of admissions due to poisoning and to find out various type of poisoning and related mortality. Methods: The secondary data was collected from records available in Intensive care unit of toxicology department of tertiary care hospital. The admissions made due to various type of poisoning from Jan 2015 to Dec 2015 were included in this study. The data of nearly 947 patients were analyzed regarding to type of poising and mortality due to the poisoning. Statistical analysis like percentage, Chi-square test and mean variance significant were calculated. Results: Out of 947, 70% were male and 30% were female. Among patients admitted 44% were consumed organophosphorus compounds, 22% had snake bite and 13% were consumed rat killer paste. The other common but least were drugs, rat killer powder and kerosene poisoning. Among admitted with various type of poisoning overall mortality was 36% and 58% due to organophosphorus compounds, 16% with rate killer paste and 14% with snake bite. The snake bite mostly occurred in rainy season and it is statistically significant. Conclusions: Most of the poisoning due to organophosphorus shows that it is available very easily and also cheap. The death among the poisoning is due to delay in starting of the treatment and awareness should be made to avail medical care immediately after poisoning without delay.